Kriminalisasi Korban dalam Penegakan Hukum Digital: Analisis Yuridis Kasus Pencemaran Nama Baik Pemilik Kafe Bibi Kelinci Kopitiam dalam Perspektif Keadilan Restoratif dan Asas Ultimum Remedium - Difa Safira Grahna Anjania; Ayu Ramadhani; Puspita Amelia Anjarwati; Ferdinand Pramudita Reyhan Surendra; Anggita Aziz Azahra; Neo Adhi Kurniawan (CV. ITTC INDONESIA, 2026)
This article examines the legal phenomenon of victim criminalization in digital defamation cases, using the Nabilah O'Brien case as its primary focus. As the owner of Bibi Kelinci Kopitiam café, Nabilah initially acted as a crime victim who documented and publicized theft-related misconduct through social media CCTV footage. However, she was subsequently designated as a criminal suspect under Article 27 paragraph (3) of the Electronic Information and Transactions Law (UU ITE). Using normative juridical methods, this study analyzes the case through the lenses of restorative justice principles and the ultimum remedium doctrine. Findings indicate that the criminalization of this victim contradicts fundamental principles of legal justice, victim protection, and proportionality in criminal law enforcement. The study argues that restorative justice mechanisms represent a more appropriate and equitable resolution pathway for defamation cases arising from legitimate acts of self-documentation in digital spaces.